IMPLEMENTASI PEMBELAJARAN BAHASA INDONESIA BERBASIS TEKS DI SMP NEGERI KOTA BUKITTINGGI - Afrila, Tysa Mekar; Atmazaki, Atmazaki; Abdurahman, Abdurahman (Universitas Negeri Padang, 2018)
ABSTRACT The purpose of this research are three (1) to describe the process of implementatiom of text-based Indonesian language learning, (2) to describe the process of teaching and learning of text-based Indonesian language focused on instructional media, (3) to describe the process oftext learning based on the learning method. This research type is qualitative research by using descriptive method. Technique of data collecting is done by observation, interview, and documentation study. The result showed that teachers of SMP Negeri 4 and SMP Negeri 6 Bukittinggi have implementated four aspects ofe text-based learning that is at the stage of building the context, studying the model text, constucting guided and constructing independently, while the Indonesian language teacher at SMP Negeri 7 Bukittinggi only carried out three aspects of text-based learning, which are context-building, model review, and self-constructing. The media used in the three schools are categorically good in terms of effectiviness, relation to learning, until the use of the media itself. The use of learning methods in the three schools is alsogood in terms of its effectiviness, its relevance to learning, up to the use of the method itself. Kata kunci : implementasi pembelajaran berbasis teks, media pembelajaran, metode pembelajaran